2012
DOI: 10.1108/09540911211262539
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial IMC layer growth and tensile properties of low‐silver Cu/SACBE/Cu solder joints

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The isothermal aging of the Sn-0.7Cu solder/Ni BGA joint has been studied by Yoon et al [85]. The interaction between the Ni layer and molten solder established a (Cu, Ni Bi, Ju and Lin [3] examined the impact of introducing elemental Bi and Er to a low Ag solder alloy Sn-x(1.0, 1.5, 2.0)Ag-0.3Cu-3.0Bi-0.05Er on the development of the interfacial IMC layer (wt.%). The IMC layer thickness at the interface of a Cu/SACBE/Cu joint was discovered to be much less than that of a Cu/SAC/Cu joint.…”
Section: Effect Of Aging Time and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The isothermal aging of the Sn-0.7Cu solder/Ni BGA joint has been studied by Yoon et al [85]. The interaction between the Ni layer and molten solder established a (Cu, Ni Bi, Ju and Lin [3] examined the impact of introducing elemental Bi and Er to a low Ag solder alloy Sn-x(1.0, 1.5, 2.0)Ag-0.3Cu-3.0Bi-0.05Er on the development of the interfacial IMC layer (wt.%). The IMC layer thickness at the interface of a Cu/SACBE/Cu joint was discovered to be much less than that of a Cu/SAC/Cu joint.…”
Section: Effect Of Aging Time and Temperaturementioning
confidence: 99%
“…Moreover, the solder alloy reacts with the substrate during the soldering process, forming an interfacial IMC layer at the interface. Its development has a substantial impact on the solder joint's reliability [3]. In soldering, a thin coating of interfacial intermetallic is recommended to establish effective metallurgical bonding at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a coating of Ni over the Cu metallization is often used as a diffusion barrier (Chan et al, 2002). Studies have been reported on the reaction of different solders with Cu substrates (Ju et al, 2014;Zhu and Sun, 2017;Bi et al, 2012;Yan et al, 2016) and Ni/Cu substrates during reflow and ageing (Huang and Lin, 2004;Lee et al, 2005;Mittal and Lin, 2012;Mittal and Lin 2014;Tian et al, 2003). Reaction of Sn-Ag, Sn-Cu and Sn-Bi solders with Ni substrates leads to the formation of Ni 3 Sn 4 IMC, whereas the Sn-Zn solder alloy reacts with Ni to form the Ni 19 Zn 80 Sn IMC (Chan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of researches have been done to solve these problems, for example, adding a certain content of Bi in SAC0307 can reduce the melting point of solder and improve the wettability 7) . The addition of Bi or Be in the SAC solder could limit the growth of the intermetallic compound (IMC) and improve the mechanical properties of solder 8,9) . A kind of low-temperature stirring soldering of low-silver SAC solder was studied by Gan, which found that the IMC growth of joint was signi cantly inhibited by adding Ni nanoparticles 10,11) .…”
Section: Introductionmentioning
confidence: 99%